Exocyclic DNA adducts as secondary markers for oxidative stress: applications in human cancer etiology and risk assessment - Bartsch, Helmut; Nair, Jagadeesan (Biological reactive intermediates VI, 2001)
DNA-bound carcinogen adducts reflect the amount of an exogenous chemical or its metabolite that covalently interacted with nucleic acid bases at the target site (biologically effective dose) or in surrogate tissues. DNA adducts are mechanistically more relevant to carcinogenesis than internal doses of genotoxins, since they take into account interindividual differences in metabolism and of DNA repair capacity.
Gesehen am 12.01.2001